Analisis Gamifikasi Fill-in-the-Blank dengan Evaluasi Otomatis Abstract Syntax Tree Pada Pembelajaran Python - Margaretha Violina Putri; Usman Nurhasan; Hendra Pradibta (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
This study develops and implements a Fill-in-the-Blank (FIB)-based learning system with gamification and automatic evaluation using Abstract Syntax Tree (AST) in Basic Python Programming learning. The applied methodology combines Research and Development (R&D) to design a prototype and Quasi-Experiment with a pre-test, post-test design on the experimental group (n=26) and control group (n=25). Needs analysis through literature, lecturer interviews, and classroom observations resulted in an interactive system with points, levels, and badges mechanisms. Measurement instruments include AST evaluators, concept understanding tests, motivation questionnaires, and student activity logs. The System Usability Scale (SUS) results averaged 76.47, indicating the system is easy to use and well-accepted. Blackbox testing confirmed that all features function as designed. Quasi-Experiment analysis showed a significant improvement in the experimental group, from Pre-Test 27.45 to Post-Test 92.92 (Paired Sample T-Test, p = 0.000) with stable retention in the Delay-Test 81.84 (p = 0.087), while the control group only improved limitedly. Independent Sample T-Test also proved a significant difference between the experimental and control groups. These findings demonstrate the effectiveness of the FIB system in improving learning outcomes, comprehension retention, and interactive learning experiences.Keywords: Abstract Syntax Tree; Fill-in-the-Blank; Gamification; Python Programming; Learning SystemAbstrakStudi ini mengembangkan sistem pembelajaran Fill-in-the-Blank (FIB) berbasis gamifikasi dan evaluasi otomatis Abstract Syntax Tree (AST) untuk pembelajaran Python dasar. Metode yang digunakan menggabungkan Research and Development (R&D) dalam perancangan prototipe dan Quasi-Experiment dengan desain pre-test dan post-test pada kelompok eksperimen (n=26) dan kontrol (n=25). Analisis kebutuhan menghasilkan sistem interaktif dengan fitur poin, level, dan lencana. Instrumen evaluasi meliputi AST evaluator, tes konsep, kuesioner motivasi, dan log aktivitas. Hasil System Usability Scale (SUS) mencapai 76,47, menunjukkan sistem mudah digunakan. Uji blackbox memastikan seluruh fitur berfungsi sesuai rancangan. Hasil eksperimen menunjukkan peningkatan signifikan pada kelompok eksperimen dari 27,45 ke 92,92 (p = 0,000) dan retensi stabil 81,84 (p = 0,087), sementara kelompok kontrol hanya meningkat terbatas. Secara keseluruhan, sistem FIB terbukti efektif meningkatkan hasil belajar, retensi pemahaman, dan pengalaman belajar interaktif.